BSAVA manual of Canine and Feline dentistry (British Small Animal Veterinary Association, 2007)
The focus of this book is exclusively cats and dogs, allowing for a better, reorganized central focus which offers both anatomy and discussion of dental health and operator safety. Color photos throughout an chapters dedicated to conditions which occur in cats or dogs makes for an outstanding reference